Tourists’ perceived value and satisfaction in a community-based homestay in kampung Parit Bugis, Muar, Johor - Amit, Nur`Ain; Md Sawari, Siti Salwa (2019)
The homestay program was getting recognition since the early of 2000’s. It is one of the contribution to the country’s economy. However, there are less study made for measuring the effect on perceived value and satisfaction of a tourist staying in the homestay. Thus, this study aims to examine the effects on perceived value on the satisfaction on tourists that stays in the homestay. A total of 30 respondents from the homestay program participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 through several analyses such as descriptive analysis, frequency analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis which was focused into three aspects which is functional, emotional, and social value. The outcomes of this study show how a strong positive effect for perceived value on the satisfaction of homestay guests. In addition, the results demonstrate the acceptability of perceived value as an integrated construct formed by the dimensions identified. This study shows that the relatonship between the homestay and the guest requires the overal perceived value that leads to more visitors joining the homestay programme in the future